Pendekatan Konsep Harmoni dalam Manajemen Konflik oleh Jepang dalam Isu Sengketa Senkaku/Diaoyu dengan Tiongkok - Saeputra, Rudi (Global: Jurnal Politik Internasional, 2018)
The Senkaku dispute refers to a territorial claim between China and Japan over a group of eight pinnacle islands in East China Sea. Japan has taken a valid control over the Senkaku Islands since 1895. Yet, in the light of historical records, China claims the islands as a part of its ancient territory. This article aims to analyze Japan’s motives in taking repetitive peaceful measure in handling the Senkaku/Diaoyu Islands dispute. Most of existing academic writing about China-Japan discord put emphasize on the findings related to mutual aid and regime, strategy and policy, power projection and threat perception, and interaction of complex relationship. Few, if any, scrutinize Japan’s concern to take non-violent way to face China in the Senkaku/Dioayu dispute. By applying harmony-concept-invoked-approach of conflict management, this article goes for cultural philosophy and national interests as motives behind Japan’s repetitive peaceful measure in the Senkaku/Diaoyu dispute. This article shows that the Japan’s non-violent measure is induced by her value of traditional culture along with economy factor and national security.